2018
DOI: 10.3389/fped.2018.00131
|View full text |Cite
|
Sign up to set email alerts
|

The KOUNCIL Consortium: From Genetic Defects to Therapeutic Development for Nephronophthisis

Abstract: Nephronophthisis (NPH) is the most common monogenic cause of renal failure in children. Treatment options are limited to dialysis and transplantation. Therapeutics to significantly delay or prevent end-stage renal disease (ESRD) in children are currently not available. In the Dutch-Anglo KOUNCIL (Kidney-Oriented UNderstanding of correcting CILiopathies) consortium, several groups and specialties united to perform scientific groundwork with the aim to develop genetic and therapeutic personalized care for NPH pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Any genetic testing should be done with appropriate pre-test counselling. Molecular confirmation of NPHP is possible in about 60% of affected individuals by identifying the pathogenic variants in the NPHP-associated genes [ 1 , 13 , 14 ]. Our patient was found to have an autosomal recessive inheritance of the NPHP3 gene with compound heterozygous variants: a pathogenic variant (p.E145Vfs*3) inherited from her father and a likely pathogenic variant (p.K144E) inherited from her mother.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Any genetic testing should be done with appropriate pre-test counselling. Molecular confirmation of NPHP is possible in about 60% of affected individuals by identifying the pathogenic variants in the NPHP-associated genes [ 1 , 13 , 14 ]. Our patient was found to have an autosomal recessive inheritance of the NPHP3 gene with compound heterozygous variants: a pathogenic variant (p.E145Vfs*3) inherited from her father and a likely pathogenic variant (p.K144E) inherited from her mother.…”
Section: Discussionmentioning
confidence: 99%
“…There are about 25 known gene-disease associations with NPHP and most of these variants result in loss of function of the proteins [ 5 , 14 ]. Proteomic studies have revealed these proteins form macromolecular complexes known as nephrocystin modules, which work simultaneously to support cilio-genesis and ciliary function [ 5 , 14 ]. Nephrocystin 1 encoded by NPHP1 , is an adaptor protein found on primary cilia and renal epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Induced pluripotent stem cells (iPSCs) technology may be a powerful tool to facilitate personalized drug assessment as iPSCs can be derived from fluids and tissues that are easy to obtain (blood, fibroblasts and urine) and can subsequently be differentiated into cells of a relevant tissue. Thus, a personalized approach for drug screening and gene-based therapy may be the future direction for individuals diagnosed with Sensenbrenner syndrome [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Access to and cost of genetic testing is variable, in some countries being available only in research units [323], and often with significant turnaround time. Despite this, implementation of testing and registries has allowed the creation of comprehensive databases of genotype-phenotype correlation, which will help with future diagnosis [324]. Registries exist in the USA [56], China [325], Germany, Austria, and Denmark [318], and Holland [326].…”
Section: Diagnosis Screening and Preventionmentioning
confidence: 99%